High-fidelity Glucagon-CreER mouse line generated by CRISPR-Cas9 assisted gene targeting - Amanda M. Ackermann; Jia Zhang; Aryel Heller; Anna Briker; Klaus H. Kaestner (Elsevier, 2017)
Objective: α-cells are the second most prominent cell type in pancreatic islets and are responsible for producing glucagon to increase plasma glucose levels in times of fasting. α-cell dysfunction and inappropriate glucagon secretion occur in both type 1 and type 2 diabetes. Thus, there is growing interest in studying both normal function and pathophysiology of α-cells. However, tools to target gene ablation or activation specifically of α-cells have been limited, compared to those available for β-cells. Previous Glucagon-Cre and Glucagon-CreER transgenic mouse lines have suffered from transgene silencing, and the only available Glucagon-CreER "knock-in" mouse line results in glucagon haploinsufficiency, which can confound the interpretation of gene deletion analyses. Therefore, we sought to develop a Glucagon-CreERT2 mouse line that would maintain normal glucagon expression and would be less susceptible to transgene silencing. Methods: We utilized CRISPR-Cas9 technology to insert an IRES-CreERT2 sequence into the 3' UTR of the Glucagon (Gcg) locus in mouse embryonic stem cells (ESCs). Targeted ESC clones were then injected into mouse blastocysts to obtain Gcg-CreERT2 mice. Recombination efficiency in GCG+ pancreatic α-cells and glucagon-like peptide 1 positive (GLP1+) enteroendocrine L-cells was measured in Gcg-CreERT2;Rosa26-LSL-YFP mice injected with tamoxifen during fetal development and adulthood. Results: Tamoxifen injection of Gcg-CreERT2;Rosa26-LSL-YFP mice induced high recombination efficiency of the Rosa26-LSL-YFP locus in perinatal and adult α-cells (88% and 95%, respectively), as well as in first-wave fetal α-cells (36%) and adult enteroendocrine L-cells (33%). Mice homozygous for the Gcg-CreERT2 allele were phenotypically normal. Conclusions: We successfully derived a Gcg-CreERT2 mouse line that expresses CreERT2 in pancreatic α-cells and enteroendocrine L-cells without disrupting preproglucagon gene expression. These mice will be a useful tool for performing temporally controlled genetic manipulation specifically in these cell types. Keywords: Islet, α-cell, Enteroendocrine L-cell, Glucagon, GLP1, CRISPR